2021
DOI: 10.1002/csr.2209
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of integrated reporting and changes to internal mechanisms in Japanese companies

Abstract: The increase in companies' use of integrated reporting (IR) has led to an increase in academic interest in IR. However, IR research from an internal corporate perspective is limited. This study investigates the approaches and internal mechanisms that early adopters use to implement IR. Further, the study examines whether IR drives organisational change at an early stage. A multiple case study was conducted. Data were collected through semi‐structured interviews and email exchanges with the managers responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…In general, previous IR research has dealt primarily with conceptual issues, such as appreciations and criticisms of IR, with normative advice on the implementation of IR practice (Veltri & Silvestri, 2020), or alternatively, with the approaches and internal mechanisms that early adopters use to implement IR (Hosoda, 2021). By contrast, empirical studies in the field are still relatively scarce (Veltri & Silvestri, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In general, previous IR research has dealt primarily with conceptual issues, such as appreciations and criticisms of IR, with normative advice on the implementation of IR practice (Veltri & Silvestri, 2020), or alternatively, with the approaches and internal mechanisms that early adopters use to implement IR (Hosoda, 2021). By contrast, empirical studies in the field are still relatively scarce (Veltri & Silvestri, 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A recent study based on interviews and multiple case studies discovered that the early IR adopters observed accelerated promotion and practiced integrated thinking at the first level (Hosoda, 2022). However, the awareness of integrated thinking was weaker at lower levels of the organization in the Japanese and UK markets (Agarwal and Kallapur, 2018; Hosoda, 2022). These studies observed that the use of integrated thinking can promote changes in internal mechanisms and organizational value toward the creation of long-term value.…”
Section: The Materiality Of Risk Information In Integrated Reportingmentioning
confidence: 99%
“…10, 100 or 1,000) (Jørgensen et al , 2022; Abraham and Shrives, 2014; Elshandidy et al , 2018). This issue has impacted risk reporting at extremely low or high numbers, which cannot be linked to integrated thinking (Hosoda, 2022; Adams, 2015; Adams et al , 2007). To handle this challenge, organizations frequently use a reasonable calculation (risk with high probability or frequency) (Mikes, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature pays little attention to grasping the way that the IR adoption process is stimulated by internal organisational change (Perego et al, 2016), and the internal mechanisms and approaches which the IR adapters employ are poorly understood (de Villiers et al, 2017ba;Gibassier et al, 2018;Guthrie et al, 2017;Hosoda, 2021;. Scholars have recently performed more qualitative studies on the drivers of IR (Hossain et al, 2023).…”
Section: Introductionmentioning
confidence: 99%